Early Childhood Education: Innovative Pedagogical Approaches in the Post-modern Era - Ampartzaki, Maria, Ed (IntechOpen, 2023)
This book discusses innovative approaches that employ transformative elements (targets, methods, materials, ideas, etc.) in early childhood education. It embraces integrated approaches and conceptualizations, such as the concept of “edu-care,” which signifies the inseparability of care and education. Further, it examines the implementation of the STEM and STEAM approaches at the microlevel of a classroom and at the country level to get a grasp of the degree of implementation and stakeholders’ understanding. It also presents a well-documented attempt at the creation of “transformative” learning experiences for young children through an online course on local history. The book ends with some concluding remarks on the application of post-modernist ideas in early childhood education.